The Relevance of Religious Knowledge in the Digital Age: A Quranic Guide for the Modern Generation - Rohanita, Lailatur; Azizah, Mar’atul Fitriayu; Sholihah, Sholihah; Mirrohmatillah, Mirrohmatillah; Aini, Nurul (Journal of Modern Islamic Studies and Civilization, 2025)
The modern generation, which is closely related to digitalization, needs guidance in using various social media. By delving deeper into the relevance of religious knowledge in the digital era through the guidance of the Qur'an, the modern generation can build ethics in communicating and socializing to create a healthy digital space. The descriptive qualitative research method is used to explore information through a library research approach so that the information obtained is more in-depth. The study of Surah Al-Hujurat verse 11 on communication ethics implies that communication is a crucial aspect of community life that must be carried out by upholding moral and ethical values. It should emphasize the importance of maintaining manners in communicating, such as not mocking, criticizing, using bad titles, having negative prejudices, finding fault, or talking about other people's bad points. The noble values ​​contained in this verse, such as mutual respect, tolerance, good intentions, and monotheism, are the main foundations in building harmonious social interactions, both directly and in digital spaces. In the modern era, applying these principles is a strategic solution to overcome communication challenges in the digital era, including phenomena such as cyberbullying, by encouraging the creation a more positive and respectful digital environment. Moral education based on Islamic teachings plays a significant role in instilling noble behavior so that society can face the development of the times, always adhere to the values ​​of the Qur'an, and make the Prophet Muhammad SAW the primary role model.